Implementasi Prinsip Pembelajaran Mendalam Dalam Perencanaan Pembelajaran Bahasa Indonesia Kelas VII - Titis Kusumaningrum Witdaryadi Putri; Diantri Seprina Putri; Faisal Isnan (Prawara: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2026)
This study aims to analyze the implementation of deep learning principles, namely mindfulness, meaningful learning, and joyful learning, in Indonesian language lesson planning for Grade VII students at the junior secondary level. The study is grounded in the importance of instructional planning that extends beyond content mastery to emphasize the quality of students' learning experiences. A descriptive qualitative approach was employed, with data sources comprising lesson planning documents for news texts, descriptive texts, and procedural texts. Data were analyzed using content analysis techniques based on indicators derived from deep learning principles. The findings indicate that all three principles have been incorporated; however, they have not been consistently integrated as a coherent pedagogical orientation. Meaningful learning emerged as the most dominant principle, while mindfulness and joyful learning tend to be implemented procedurally and situationally. These findings highlight the need to strengthen lesson-planning practices that are more reflective and explicitly student-centered.